2010
DOI: 10.1371/journal.pone.0009681
|View full text |Cite|
|
Sign up to set email alerts
|

Cross-Presentation of a Spread-Defective MCMV Is Sufficient to Prime the Majority of Virus-Specific CD8+ T Cells

Abstract: CD8+ T cells can be primed by peptides derived from endogenous proteins (direct presentation), or exogenously acquired protein (cross-presentation). However, the relative ability of these two pathways to prime CD8+ T cells during a viral infection remains controversial. Cytomegaloviruses (CMVs) can infect professional antigen presenting cells (APCs), including dendritic cells, thus providing peptides for direct presentation. However, the viral immune evasion genes profoundly impair recognition of infected cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
90
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 34 publications
8
90
0
Order By: Relevance
“…Nevertheless, this work provides evidences that in the case of MCMV infection, the presence of cross-presenting DCs strongly promotes priming of CD8 1 T-cell responses, which is in line with recently published results, where MHC class I-deficient fibroblasts, infected with a spread-defective mutant of MCMV, were used to assess the role of cross-presentation in the priming of MCMV-specific CD8 1 T-cell responses [25]. However, subsequent shaping of the virus-specific CD8 1 T-cell response in the presence of latent/reactivating infection is largely independent on cross-presenting DCs, at least for two of the three inflating specificities, which seem sensible as viral reactivation events should be controlled instantaneously and in a targeted manner focusing on actually infected cells in an immune host.…”
supporting
confidence: 91%
“…Nevertheless, this work provides evidences that in the case of MCMV infection, the presence of cross-presenting DCs strongly promotes priming of CD8 1 T-cell responses, which is in line with recently published results, where MHC class I-deficient fibroblasts, infected with a spread-defective mutant of MCMV, were used to assess the role of cross-presentation in the priming of MCMV-specific CD8 1 T-cell responses [25]. However, subsequent shaping of the virus-specific CD8 1 T-cell response in the presence of latent/reactivating infection is largely independent on cross-presenting DCs, at least for two of the three inflating specificities, which seem sensible as viral reactivation events should be controlled instantaneously and in a targeted manner focusing on actually infected cells in an immune host.…”
supporting
confidence: 91%
“…This pointed to a prominent role for cross-presentation, but left open whether the residual T cell priming observed resulted from direct priming or from other remaining APCs in these mice that are capable of cross-presentation. Using a spread-defective MCMV mutant, Snyder et al (54) reported that cross-presentation is sufficient to generate an MCMV-specific CD8 + T cell response that is qualitatively similar to that observed after infection with replication-competent MCMV-wt. However, it remained unclear whether the quantitative difference in the T cell response was due to limiting amounts of viral Ag or to the absence of direct presentation.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, the T cell response will be biased toward such viral Ags that are good substrates for cross-presentation. For the development of a CMV vaccine and for use of CMV as a vaccine vector against other pathogens (91)(92)(93), it is therefore recommended to use stable, long-lived Ags that can be cross-presented, as was proposed previously (54). The concern that deletion of vRAP genes reduces the efficacy of a live CMV vaccine (84) may be of less importance because this will probably lead to desired attenuation of a vaccine and, as we show in this study, will not affect the Ag presentation pathway, and hence in accordance with the experimental findings (36), will not influence the specificity of the induced T cell response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, a live, attenuated vaccine approach has several characteristics that render it attractive. Unlike subunit vaccines, which induce cellular or humoral immune response to selected antigens only, live vaccines induce a much broader immunity that may mimic protection acquired following natural infection (31,33,(66)(67)(68)(69). Cellular immunity against CMV follows unique kinetics characterized by maintenance or even expansion of the virus-specific CD8 + T cell response over time (70,71).…”
Section: Discussionmentioning
confidence: 99%